Collaborative And Multidisciplinary Strategies In Infection Prevention And Control: A Literature Review Across Healthcare Professions (The Review of Diabetic Studies, 2024)
Introduction: Multidisciplinary partnership in infection prevention and control involves the combination of clinical, behavioral, epidemiological, pharmaceutical, and social knowledge towards minimizing healthcare-associated infections and patient safety improvement. Interprofessional collaboration in healthcare guarantees multi-company approaches and integrated actions.Aim: The research is also going to address the role and contributions of different health care professionals to infection prevention and control, evaluating the benefits of a multidisciplinary approach to the prevention and control of infections and overcoming obstacles.Methods: Quantitative and qualitative information regarding clinical, rehabilitation, epidemiology, pharmaceutical, and public health professionals will be collected using a mixed-method study design that involves the administration of structured questionnaires, semi-structured interviews, focus groups, and direct observation.Findings: Multidisciplinary teamwork promotes the use of improved infection surveillance, patient compliance, medication management practices, vectors, and rehabilitative services, whereas obstacles like communication disturbances, behavioral issues, and resource constraints are reduced by organizing team efforts.Conclusion: The combination of various healthcare skills in infection control is beneficial to patient safety, infection rates, system resilience, ethical, and sustainable practice in the healthcare environment.